Analysis of Lateral Force and Base Shear Due to Earthquake Loads Based on Yield Point Spectra - Goldelfridus Alfredo Abani; Krisantos Ria Bela; Krisantus Satrio Wibowo Pedo (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2024)
Earthquakes pose a significant challenge in structural engineering, as they expose buildings to strong lateral forces that can cause severe damage or even collapse. One important aspect of this analysis is to determine the lateral forces and base shear acting on the structure. The purpose of this study is to obtain the values of lateral forces and base shear in structures using the yield point spectra method. The yield point spectra is a graph that relates the yield shear strength coefficient (Cy) and the displacement at yield (Δy) with a certain ductility, Aschheim and Black (2000). The calculation results show that the base level shear determined using the yield point spectrum is smaller Viβ = 1599.93 kN compared to the base level shear obtained using SNI 1726-2019 which is greater Vi = 1656.57 kN. The level shear value at the top level with the equation suggested by Chao et al. (2007) and the Building Seismic Safety Council (2009) is higher by Fi,β = 640.56 kN, compared to the level shear value determined using SNI 1726-2019, smaller Fi = 444.75 kN according to the level shear value based on the shear ratio. It can be concluded that the smaller the base shear and upper level shear in the building structure, the smaller the risk of damage or collapse of the structure due to earthquakes.